Identifying the fuels and energy conversion technologies necessary to meet European passenger car emissions legislation to 2020 - Bishop, J; Axon, C; Tran, M; Bonilla, D; Banister, D; Mcculloch, M (Elsevier, 2012)
The focus of European emissions legislation for light goods vehicles centres on tank-to-wheel (TTW) operation, despite the importance of the well-to-tank (WTT) impacts of supplying transport fuels. This work presents defensible calculations of best estimate and best-in-class WTT pathways to supply conventional and non-conventional fuels. These estimates are weighted by the availability of resources. The best estimate pathway is the peak of the distribution of WTT estimates obtained from the literature. The best-in-class pathway has the lowest greenhouse gas (GHG) emissions per unit of fuel delivered and represents the state-of-the-art. These fuel pathways are paired with energy conversion (vehicle) technologies and compared with equivalent well-to-wheel (WTW) targets for 2015 and 2020. Of the 103 best estimate fuel-vehicle combinations, 42 meet the 2015 emissions legislation. By 2020, only 17 combinations meet the more strict emissions limit. Petrol production will require net negative GHG emissions, even if blended with bioethanol, to meet the equivalent WTW 2020 target. For the three main combustion energy-conversion technologies, a median efficiency improvement of 29% is required when paired with the best estimate fuel pathways. However, using best-in-class pathways indicates that all of the energy conversion technologies can meet the revised 2015 target, but some still fail to meet the 2020 target. Improvements in TTW technologies alone will not meet the legislative targets, and many fuel-vehicle combinations cannot deliver an overall reduction in GHG emissions.